Narratives around family-controlled groups and their Corporate Governance : Case Samsung and Wallenberg - Paavilainen, Eeva (My University, 2024)
This thesis investigates corporate governance practices within large family-controlled groups, focusing on two prominent conglomerates: the Wallenberg Group in Sweden and Samsung in South Korea. The study comprises a comprehensive literature review of corporate governance principles both globally and within the specific contexts of Scandinavia and Korea. The empirical component of the study employs a narrative analysis methodology to examine the corporate governance structures and practices of the Wallenberg Group and Samsung. Drawing on primary and secondary data sources, including company reports, financial statements, and news, the narrative analysis uncovers key themes, narratives, and patterns within each case company. The findings highlight the significance of family influence, cultural norms, legal frameworks, and institutional environments in shaping corporate governance dynamics. While both conglomerates exhibit efforts to align with global governance standards, notable variations emerge in terms of ownership structures, board compositions, transparency measures, and stakeholder relations. This thesis contributes to the existing literature by offering insights into the complexities of corporate governance within large family-controlled groups, within the distinct business landscapes of Sweden and Korea. The narrative analysis approach provides an understanding of the governance practices and challenges faced by these conglomerates, and the focus on the perception of the corporate governance gives reader the collected image of the governance models.
Keywords: corporate governance, family-controlled company, conglomerate, narrative analysis